Alterações comportamentais em ratos administrados com preparações da Datura suaveolens - Silva, Eli Sinnott; Abreu, Silvia Machado; Argoud, João José B; Silveira, Simone Nascimento; Silva, Fernando Amarante; Almeida, Tabajara Lucas de (VITTALLE - Revista de Ciências da Saúde, 2017)
Ver no documento.